A clinical study of the role of split-thickness skin autograft in management of wounds and identification of factors influencing the graft uptake - Haris, Shafiqa; Nema, Prashant Kumar; Charokar, Kailash; Gupta, Nitin (International Surgery Journal, 2025)
Background: Wound management is a significant concern in surgical care, with split-thickness skin grafting (STSG) being a common treatment option. To evaluate the clinical outcomes of STSG in wound management and identify factors influencing graft uptake. Methods: This observational descriptive study was conducted at a tertiary care center among patients requiring STSG for wound management. Patients were followed up for 3 months post-STSG. Results: A total of 40 patients were enrolled. Diabetes, hypoproteinemia, and positive wound culture was significantly associated with partial graft loss (p<0.05). The duration of the ulcer was significantly longer in patients with graft loss (p<0.05). Pain scores improved significantly after grafting in both patients with and without graft loss. Complications such as serous discharge were more common in patients with partial graft loss. Conclusions: This study highlights the importance of optimizing wound conditions and addressing underlying comorbidities to improve graft outcomes. Diabetes, hypoproteinemia, and positive wound culture were identified as significant factors influencing graft uptake.